2 In-vivo diffusion tensor cardiovascular magnetic resonance detects the arrangement and dynamic nature of right ventricular microstructure in health and disease. (28th January 2023) - Nielles Vallespin, Sonia; Ferreira, Pedro; Scott, Andrew; Roehl, Malte; McCarthy, Karen; Smith, Gillian C; Yen Ho, Siew; Li, Wei; Pennell, Dudley J; Babu-Narayan, Sonya V
Abstract : Introduction: Right ventricular (RV) function is of prognostic importance in acquired and congenital heart disease. Understanding the relationship between myocardial microstructure and function may help explain why some patients do better than others. We used in-vivo diffusion tensor cardiovascular magnetic resonance (DT-CMR) to investigate normal RV microstructure and in the setting of the RV at systemic pressure Materials and Methods: DT-CMR was acquired in 10 volunteers and 19 patients with a systemic RV (SRV) after atrial re-direction surgery for transposition of the great arteries. Cardiomyocyte orientation (E1) and the angle of cardiomyocyte sheetlets (absolute E2A) was measured. E2A mobility was defined as the difference in absolute E2A between diastole and end-systole. Results: In the compact RV, cardiomyocyte orientation was within a circumferential range, with progressive change throughout the ventricle. In trabeculations, orientation of RV cardiomyocytes was predominantly longitudinal. Figure 1 . A similar pattern was seen in volunteers and patients. Absolute E2A in both the RV free wall and septum increased from diastole to end-systole in all participants, demonstrating dynamic microstructural re-arrangement. The SRV demonstrated similar E2A mobility compared with the normal RV (26.1±10.8° vs 26.4±9.2°). In the SRV septum, E2A mobility was reduced compared with the normal heart (21.1±14.9° vs 48.1±10.2°; p<0.001) Discussion: Dynamic microstructural re-arrangement is suggestive of functional RV sheetlets. We demonstrated reduced sheetlet E2A mobility in the SRV septum compared with the normal heart, suggesting impaired dynamic motion of septal microstructure in these patients. Conclusion: We have demonstrated the arrangement of cardiomyocytes of the human RV in-vivo, in the normal heart and in an extreme model of right ventricular dysfunction. This opens the door to future study of the potential associations of DT-CMR and clinical status in patients with RV disease. Acknowledgements: With thanks to Ricardo Wage and Raj K Soundarajan who provided technician support for the CMR studies.